CLINICAL AND IMMUNOLOGICAL СHARACTERISTICS OF ACUTE NECROTIZING FORM OF CUTANEOUS LEISHMANIASIS - О.U. OLISOVA; Т.О. SAIDINOVA; М.S. ISAEVA (Avicenna Tajik State Medical University, 2017)
Objective: To study immunological disorders in patients with a rural (acute necrotizing) form of Cutaneous Leishmaniasis (CL). Methods: 80 patients were found under the observation in a rural (acute necrotizing) form of CL, including 23 (28.8%) men and 57 (71.2%) of women. The age of patients fluctuated from 16 to 60 years and over Results: The data showed that the oppression of the activity of the cellular immunity in patients with CL in comparison with healthy people, which indicates the significant of absolute and comparative numbers of CD3 lymphocytes (by 20%, p<0.01), the tendency of falling of absolute and comparative numbers of CD4 (T helper-inducers) and CD8 (T-cytotoxic) lymphocytes (correspondingly to 12% and 18%), as well as the absolute and comparative number of lymphocytes (by 12%) of peripheral blood. Conclusion: Thereby, in patients with acute necrotizing form of CL observes immunological disorders both in cellular and humoral components of immunity, which was depended on prescription of the process and the presence of complications.